THE CARE OF THE SELF AS AN EXPERIENCE OF THOUGHT: A REFLEXION FROM AN INFORMAL SPACE OF EDUCATION - Gelamo, Rodrigo Pelloso [UNESP]; Sanabria Aleluia, Jose Roberto; Valim Rosa, Alvaro Matheus [UNESP] (Univ Estadual Campinas, Fac Educacao, 2019)
This article aims to reflect on theoretical and practical activities developed in the project Transmitting knowledge or experience in Philosophy teaching: limits and possibilities. The project aimed to relate academic and daily knowledge in order to satisfy demands and needs that would consider the reality of educators, students and pre-service teachers involved in the process of developing the proposed activities. Specifically, the project aimed to provide philosophical experiences, without relying on methodologies or teaching practices that would justify the traditional structure of content transmission. We have started from the idea that it was possible to break with the logic of explanation of the figure of the teacher, which produces conditioned teachings and, therefore, justifies our choice for an informal space. This led us to ground our experiences outside the academic space, on the notions of care of the self and care of the other, by Michel Foucault, presence and poetics of transmission, by Fernando Barcena, and logic of explanation, by Jacques Ranciere.
Keywords: Care of the Self; Biopolitics; Philosophy teaching; Enlightment